Factors Affecting Sustainable Performance of Construction Projects during Project Life Cycle Phases - Enshassi, Adnan; Kochendoerfer, Bernd; Al Ghoul, Hadeel (International Journal of Sustainable Construction Engineering and Technology, 2016)
Sustainable development (SD) is one of the main challenges faced by the construction industry, which has acquired global attention. Sustainable performance (SP) of a construction project during its life cycle (LC) is considered crucial to achieve the SD. The aim of this paper is to investigate the factors affecting sustainable performance of construction projects throughout project life cycle phases in the Gaza Strip. A total of 53 sustainable factors (economic, social, and environmental sustainable factors) were identified through extensive literature review and confirmed by experts’ interviews and a pilot study. These factors are classified in relation to the project life cycle phases; inception phase, design phase, construction phase, operation phase, and demolition phase. A structured questionnaire survey is employed in this study for primary data collection. A total of 119 questionnaires were distributed randomly to engineers working in construction projects in the Gaza Strip to solicit their views regarding the factors affecting sustainable performance of construction projects throughout project life cycle phases. The results revealed that five factors among the top ten factors that impacting the sustainable performance of construction projects are classified under the construction phase, which confirmed that the construction process has the most effect on the projects SP. Three factors are classified under the inception phase, which assured that the inception of a potential project has a considerable effect projects. In addition, one factor was classified under operation phase and one factor was classified under demolition phase. The most common factors affecting the SP of construction project through the overall sustainability elements: reusable/recyclable element, provision of services, energy consumption, water cost, and water pollution assessment. Further studies are recommended to explore how to integrated sustainability concepts into the whole construction process in order to achieve sustainable construction project.